2006
DOI: 10.1095/biolreprod.106.051805
|View full text |Cite
|
Sign up to set email alerts
|

Decidualization Regulates the Expression of the Endometrial Chorionic Gonadotropin Receptor in the Primate1

Abstract: Chorionic gonadotropin (CG) plays an important role in establishing a receptive endometrium by directly modulating the function of both endometrial stromal and epithelial cells in the baboon. The focus of this study was to characterize changes in CG receptor (LHCGR, also known as CG-R) expression during the menstrual cycle and early pregnancy, particularly during decidualization. LHCGR was localized by using a peptide-specific antibody generated against the extracellular domain. Immunostaining was absent in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
5
29
0
Order By: Relevance
“…Additionally, hCG messenger RNA (mRNA) is transcribed as early as the two-cell stage of the embryo (47), and the hCG protein is already being secreted by the embryo before implantation (48,49). Thus, there appears to be an effect of hCG on the regulation of the endometrium and on implantation (50)(51)(52)(53). The addition of LH activity in the form of hMG or recombinant LH has been associated with an increase in implantation rates (11,38,54,55), although other studies have not confirmed this finding (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hCG messenger RNA (mRNA) is transcribed as early as the two-cell stage of the embryo (47), and the hCG protein is already being secreted by the embryo before implantation (48,49). Thus, there appears to be an effect of hCG on the regulation of the endometrium and on implantation (50)(51)(52)(53). The addition of LH activity in the form of hMG or recombinant LH has been associated with an increase in implantation rates (11,38,54,55), although other studies have not confirmed this finding (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as pregnancy progresses, subsequent decidualization results in the downregulation of the LH/CG receptor, thought to be a prerequisite for the morphological transformation of stromal cells in the endometrium. This reduction in receptor expression corresponds to a decrease in CG in peripheral circulation [22].…”
Section: Molecular Biology Of Cgmentioning
confidence: 91%
“…The CG receptor is ubiquitously expressed in reproductive organs [10,11]. Targeted deletion of the CG receptor results in an altered endometrial phenotype and disrupted gene expression [12].…”
Section: Molecular Biology Of Cgmentioning
confidence: 99%
“…Apart from the classical hormones E 2 and P, hCG has an influence on the maternal endometrium and the process of implantation (20)(21)(22)(23)(24)(25). These effects are mediated by hCG/ LH-receptors expressed in the endometrium, which show a special cycle-dependent profile of expression (26)(27)(28). We recently have been able to demonstrate that hCG reduces IGF binding protein (IGFBP)-1 in decidualized endometrial stromal cells in vivo and in vitro (23,29).…”
mentioning
confidence: 99%